2020
DOI: 10.1177/1753193420905205
|View full text |Cite
|
Sign up to set email alerts
|

Time to surgery for open hand injuries and the risk of surgical site infection: a prospective multicentre cohort study

Abstract: Whether delaying surgery increases the risk of infection in open hand injuries is an important but unresolved topic. This prospective cohort study included 983 consecutive adults with open hand injuries treated surgically over 1 year. The risk ratio (RR) for surgical site infection was estimated by logistic regression. The median time from injury to surgery was 20 hours (range 4–90). Forty-one patients (4%) developed an infection. The risk of infection was not affected by the time to surgery (adjusted risk rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
3
11
1
1
Order By: Relevance
“…Yet, other factors apart from antibiotic use and time to surgery could contribute to infection rates. For example, skin loss, 17 amount of wound irrigation fluid used in the ED, 27 degree of contamination, 21,28 and age 22 could have played a role in infection rates, although we found that age was also not associated with infection rates.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Yet, other factors apart from antibiotic use and time to surgery could contribute to infection rates. For example, skin loss, 17 amount of wound irrigation fluid used in the ED, 27 degree of contamination, 21,28 and age 22 could have played a role in infection rates, although we found that age was also not associated with infection rates.…”
Section: Discussioncontrasting
confidence: 60%
“…Skin loss, however, increased the risk of infection. 17 Although Pavan et al found evidence to suggest a double peak for infection risk at the 6-and 24-hour mark, though this was not statistically significant when time to surgery was analyzed as a continuous variable. 19 Historically, there has been a 6-hour rule to surgical debridement for all open fractures.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Of the small number of studies that directly assess SSI in hand and wrist trauma, the risk ranges from 3 to 10 percent, reflecting similar risk as for all operative procedures. 8 , 13 , 14 , 15 There remains insufficient published data to reliably inform hand trauma patients of SSI risk.…”
Section: Introductionmentioning
confidence: 99%